ANALISIS POTENSI DAN EFEKTIVITAS PEMUNGUTAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KABUPATEN TUBAN - Iktama, SE, Siska; Pusposari, SE., M.Si., Ak, Devy (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study purposed to identify potential and effectiveness collection of Mineral Non Metal and Rock Tax, and strategies that should be implemented to optimize this tax revenue in District Tuban. The method of study is qualitative descriptive approach. This study uses primary and secondary data. While the techniques of data collections are by interview and documentation. The results of study are; the calculation of potential revenue of Non Metal Mineral and Rock Tax of the District Tuban during period 2006-2010 amounted to IDR 122.910.617.500. The contribution of this tax revenue to the region original revenues (PAD) shows moderate result. The effectiveness of tax collection according to the target shows result of 108.31%, it means very effective. While based on potential revenue it shows result of 78.31%, that means less effective. The strategies should be implemented to optimize it are; socializing rules to communities by involving villagers and local district officials, to control and enforce rules to the collectors officers and taxpayers, to increase the intensity of collection the tax, to increase the number of field officers, cross-checking of data and records with other agencies related to management of Mineral Non Metal and Rock, and improve infrastructure or development.